Innovativeness of Malaysian furniture industry at the firm level - Lau, Li Har (2013)
The Malaysian furniture industry is one of the main contributors to the country’s economy. However, it is losing its competitiveness and the industry needs to innovate and move up the value chain in order to survive in the competitive global market. In order to help the industry to innovate, more information on its state of innovativeness needs to be gathered. Therefore, the objectives of this study are: i. To assess the level of innovativeness of furniture firms. ii. To determine the main motivation of innovation. In order to assess the level of innovativeness of the furniture firms, the types of innovation were identified and defined. This information is then incorporated into the questionnaire, which was used in the interviews with furniture firms in Selangor. Information gathered was analysed using Correspondence Analysis to identify the innovative companies and what variables contribute to their innovativeness. These variables are then used to develop an Innovation Index for each company as well as the furniture sector. During the interviews,furniture firms were also asked on what were the main motivations for undertaking innovation activities. The answers were analysed to determine the main motivations of innovation. The first round of analysis showed that there are six Innovative companies and five Non-innovative companies. The other companies, which their Innovativeness cannot be determined, are grouped as ‘Intermediate’. Among the innovative companies, two types of behaviours towards innovation are observed. The first type is pro-active in seeking information needed for product development from various sources. The second type relies more on government and other companies within their group when carrying out innovation activities. The Non-innovative companies are found to be less Intermediate group showed that there are three types of behaviours towards innovation. The Innovation Index showed that the Innovative companies have higher scores than the Intermediate and Non-innovative companies, except for a company, which is C10. C10, which is an Intermediate company, is found to have higher score than three Innovative companies. The analysis on motivation showed that the Innovative companies are motivated by two main types of desire in carrying out innovation activities. They are the desire to compete and win (Vengeance) and the desire for social standing and attention (Status). The Intermediate companies are motivated by many more different types of desire compared to the Innovative companies. As for the Non-innovative companies, they are found to be the most affected by the desire to collect and value frugality (Saving) as well as the desire to avoid anxiety and fear (Tranquility). The level of innovativeness of Malaysian furniture firms has been successfully assessed in this study. The firms are categorised into three levels of innovativeness and the level of innovation is found to be affected by the different types of desire that motivate them. However, the survey was confined to the Selangor area due to time and financial constraints. If the survey is being extended to other states, the innovativeness level, motivation and behaviour towards innovation of furniture firms in different states could be analysed.